2015
DOI: 10.3233/bme-151349
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on verifying the detection of gait intention based on knee joint anterior displacement of gait slopes

Abstract: Abstract. This study investigated the feasibility of the Infrared (IR) sensor-based walking aids for detecting the gait intention. To compensate for the defects of Force Sensing Resistors (FSRs) or force sensors, such as the velocity control problem on gait slopes, we used IR sensors to investigate knee joint anterior displacement in order to recognize the gait intention. We also measure leg muscle activities and foot pressure, in order to verify our investigation. We placed two IR sensors on the rollator cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…When considering the influence of barrier-free sloped roads, the changes in human physical functional characteristics are obvious. It was found that the forward displacement of knee joints increased according to the slope of the road and that the region of muscle activation changed when walking on roads with different slopes [ 23 ]. However, few studies have examined the impact of sloped roads on the upper limb performance of older adults with disabilities or mobility impairments walking with walking aids.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the influence of barrier-free sloped roads, the changes in human physical functional characteristics are obvious. It was found that the forward displacement of knee joints increased according to the slope of the road and that the region of muscle activation changed when walking on roads with different slopes [ 23 ]. However, few studies have examined the impact of sloped roads on the upper limb performance of older adults with disabilities or mobility impairments walking with walking aids.…”
Section: Introductionmentioning
confidence: 99%